Apie priekaištą dėl nerelevantiškumo D. Lewiso modaliniam realizmui. - Morkūnaitė, Monika (Problems / Problemos, 2022)
The article deals with the charge of irrelevance levelled against D. Lewis's modal realism, notably known as a reductionist account of modality. The charge of irrelevance is apparently one of the most popular objections to modal realism though it often seems that the debate surrounding this charge is not very fruitful since in this context it is common to appeal, implicitly or explicitly, to different criteria for theory choice. As a result, the article deals with the problem in a slightly different manner. The article addresses arguments aimed to show that, contrary to what is often stated, modal realism does not violate our pre-theoretical intuitions, as well as arguments aimed to respond to the charge of irrelevance without appealing to criteria for theory choice at all but providing different reasons instead. However, the aim of this article is to show that all these arguments are rather unconvincing.